Humour and Feminist Activism in Literature and Other Media: Bianca Kronlöf and Liv Strömquist - Jiresch, Ester (Nordlit, 2023)
Bianca Kronlöf recently debuted as a writer with a manifesto against men's violence. Even though this work figures as a contribution to societal debate, it clearly exhibits traces of Kronlöf's feminist humor. Liv Strömquist is known for her feminist satires in form of graphic novels, in which she associates humor and biting feminist criticism with historical, philosophical and sociological theories. In my text, I examine the specifically feminist in their humor and how they utilize it to promote their (feminist) goals. Furthermore, I will answer the question of whether humor is an adequate means for feminist activism. While recent studies in feminist theory are acknowledging the importance of feminist humor in jokes, stand-up and literary works, there have not been many studies on graphic novels yet. By paying special attention to such lesser researched media, as well as the combination of different media by the activists, I will show how these cultural practices are a rich medium for ambiguous articulations of humor as multi-leveled cultural expression and an excellent vehicle for feminist ideas.